Di-[mu]-thiocyanato-[kappa]2N:S;[kappa]2S:N-bis[bis(2-methyl-1H-benzimidazole-[kappa]N3)(thiocyanato-[kappa]N)cadmium(II)] - Shaker, Shayma A.; Khaledi, Hamid; Ali, Hapipah Mohd (International Union of Crystallography, 2010)
The title compound, Cd-2(NCS)(4)(C8H8N2)(4), is a centrosymmetric dinuclear cadmium(II) complex in which each two metal ions are linked by a pair of thiocyanate N:S-bridges. Two 2-methylbenzimidazole N-atom donors and one terminal thiocyanate N atom complete a highly distorted square-pyramidal geometry around the Cd atom. In the crystal structure, two N-H center dot center dot center dot S hydrogen-bonding interactions occur, resulting in a three-dimensional polymeric structure. The apical 2-methylbenzimidazole ring and its symmetry-related counterpart are arranged in an antiparallel manner with a centroid-centroid separation of 3.6050 (14) angstrom, indicative of a pi-pi interaction.